The Clinical Significance of Uric Acid and Complement Activation in the Progression of IgA Nephropathy - Yasar Caliskan; Yasemin Ozluk; Dilara Celik; Nida Oztop; Aysun Aksoy; Ayse Serra Ucar; Halil Yazici; Isin Kilicaslan; Mehmet Sukru Sever (Karger Publishers, 2016)
Background/Aims: The aim of this study is to investigate the utility of clinical [age, gender, mean arterial pressure (MAP)] and laboratory parameters [eGFR, hemoglobin (Hgb), serum levels of creatinine, uric acid, albumin, proteinuria, hematuria] and also histopathological lesions (Oxford classification parameters, crescents, intensity and pattern of staining for C3, C1Q, IgA, IgG, IgM) as progression markers in patients with IgA Nephropathy (IgAN). Methods: A total of 111 IgAN patients with a follow-up period >1 year or who reached kidney failure [GFR category G5 chronic kidney disease (CKD)] Results: Mean follow-up period was 33±29 months. Thirty-seven (33.3%) patients progressed to kidney failure and 4 (3.6%) patients developed eGFR decline ≥50% from the baseline after a median of 23 and 65 months, respectively. In multivariate Cox regression analysis, baseline levels of Hgb (HR:0.782, 95% CI 0.559-0.973, p=0.037), serum uric acid (HR:1.293, 95% CI 1.023-1.621, p=0.046), eGFR (HR:0.966, 95% CI 0.947-0.984, p=0.004) and intensity of C3 staining (HR:1.550, 95% CI 1.198-1.976, p=0.049) predicted primary endpoint. Serum uric acid level was associated independently with T score (β=0.303, p=0.005) in patients with eGFR>30 ml/min/m2. Conclusions: Hyperuricemia and the deposition of C3 are independent risk factors for IgAN progression.